The Relationship Between Self-Efficacy and the Ability to Perform Physical Activities in Patients with Hypertension - Erma Dian Natalia; Dimas Ria Angga Pribadi (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hypertension is one of the major health problems in Indonesia that contributes significantly to increased morbidity and mortality due to cardiovascular disease. Physical activity has been proven effective in controlling blood pressure, but the level of compliance of hypertensive recipients with physical activity is still low. One of the psychological factors that plays a role is self-efficacy, which is an individual's belief in their ability to perform a behavior. This study aims to determine the connection between self-efficacy and the ability to perform physical activity in hypertensive patients. This study used a correlational design on 108 hypertensive patients selected through purposive sampling. The instruments used were the Exercise Self-Efficacy Scale (ESES) and the International Physical Activity-Short Form (IPAQ-SF) Indonesian version, which have good validity and reliability (Cronbach’s Alpha ESES = 0.78–0.92; ICC = 0.91; Cronbach’s Alpha IPAQ-SF = 0.884; S-CVI = 0.94). The data were analyzed using the Chi-Square test. The outcomes showed a significant connection among self-efficacy and the ability to perform physical activity (p < 0.05). These outcomes indicate that participants with high self-efficacy tend to perform moderate to high levels of physical activity contrasted to participants with low self-efficacy.